Moving from Evidence to Implementation of Breakthrough Therapies for Diabetic Kidney Disease. Issue 7 (July 2022) - Tuttle, Katherine R.; Wong, Leslie; St. Peter, Wendy; Roberts, Glenda; Rangaswami, Janani; Mottl, Amy; Kliger, Alan S.; Harris, Raymond C.; Gee, Patrick O.; Fowler, Kevin; Cherney, David; Brosius, Frank C.; et al.
Abstract : Diabetic kidney disease is the most frequent cause of kidney failure, accounting for half of all cases worldwide. Moreover, deaths from diabetic kidney disease increased 106% between 1990 and 2013, with most attributed to cardiovascular disease. Recommended screening and monitoring for diabetic kidney disease are conducted in less than half of patients with diabetes. Standard-of-care treatment with an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker is correspondingly low. Sodium-glucose cotransporter 2 inhibitors, glucagon-like peptide 1 receptor agonists, and a nonsteroidal mineralocorticoid antagonist are highly effective therapies to reduce kidney and cardiovascular risks in diabetic kidney disease. However, <20% of eligible patients are receiving these agents. Critical barriers are high out-of-pocket drug costs and low reimbursement rates. Data demonstrating clinical and cost-effectiveness of diabetic kidney disease care are needed to garner payer and health care system support. The pharmaceutical industry should collaborate on value-based care by increasing access through affordable drug prices. Additionally, multidisciplinary models and communication technologies tailored to individual health care systems are needed to support optimal diabetic kidney disease care. Community outreach efforts are also central to make care accessible and equitable. Finally, it is imperative that patient preferences and priorities shape implementation strategies. Access to care and implementation of breakthrough therapies for diabetic kidney disease can save millions of lives by preventing kidney failure, cardiovascular events, and premature death. Coalitions composed of patients, families, community groups, health care professionals, health care systems, federal agencies, and payers are essential to develop collaborative models that successfully address this major public health challenge.